Using Graphic Novels to Teach Economics Content to High School Students With Extensive Support Needs - Fitchett, Caroline; Courtade, Ginevra; Mims, Pamela J.; Landrum, Timothy J.; Sheffield, Caroline (The Journal of special education, 2025)
Despite the recognized benefit of social studies instruction, emphasis on this subject has decreased over time, and has ultimately been termed a “dispensable subject.” Social studies is an even more marginalized subject area for students with disabilities. Graphic novels (GNs) are a popular independent reading choice for both children and adults; however, only recently have GNs started appearing as instructional materials in classrooms. Using an Alternating Treatment Design (ATD), the purpose of this study was to investigate any potential differences in student outcomes (i.e., social studies content acquisition and student engagement) when using GN or traditional adapted informational text (TAIT) to teach economics concepts to high school students with extensive support needs (ESN). Another purpose of this study was to understand both classroom teachers’ and students’ perceptions of the use of GNs to teach social studies content. While this study did not demonstrate clear and consistent separation of the two conditions, there were points at which GNs appear to be associated with higher engagement and content acquisition. Another finding of this study, although not addressed as a specific research question, was that text preference appeared to predict both engagement and content acquisition.